SEJARAH HAK MILIK INTELEKTUAL DALAM ISLAM - Triyanta, Agus (Islamic University of Indonesia, 2003)
The writing below traces the history of the intellectual property rights in Islam. The concept of the intellectual property rights originates from a liberal system that ignoring exclusively the free supply and demand process. According to the writer, that Islam does not reject the urgent of the intellectual property rights because of many reasons but Islam offers the balance between the individual property rights and the rights of society in terms of protecting the intellectual property rights. In this regard, the principles of justice and social in implementation the protecting of intellectual property rights should be developed. So in the context of the strategic sources of economic, the government and muslim institution should take over the copy right.